АХМАД ИБН ХАНБАЛ ЖАНА “МУСНАД “ АТТУУ ЧЫГАРМАСЫ - АРТЫКБАЕВ, Кудрет (Scientific Journal of Faculty of Theology, 2015)
Ahmad b. Hanbal is a personality having a significant place not only in the knowledge of hadith but also in the History of Islam Culture. The Mihna Event that had happened in the Era of the Abbasid Caliphate engraved the personality and the scientific personality of Ahmad b. Hanbal. It is possible to say that the Mihna Process contributed a great value both to Ahmad b. Hanbal and to his work. The troubles he had experienced caused that he could not give a final shape to his work and his son Abdullah and his student al-Kati‘i made some additions and amendments in that work. However, that event caused various discussions.